2017
DOI: 10.1103/physreva.96.013819
|View full text |Cite
|
Sign up to set email alerts
|

Twisted molecular excitons as mediators for changing the angular momentum of light

Abstract: Molecules with C N or C N h symmetry can absorb quanta of optical angular momentum to generate twisted excitons with well-defined quasi-angular momenta of their own. Angular momentum is conserved in such interactions at the level of a paraxial approximation for the light beam. A sequence of absorption events can thus be used to create a range of excitonic angular momenta.Subsequent decay can produce radiation with a single angular momentum equal to that accumulated. Such molecules can thus be viewed as mediato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In eliciting the physics for the majority of applications discussed above, it has generally proved sufficient to use plane-wave representations of the quantum radiation modes, together with their polarization properties. Nonetheless, the same QED methods are highly amenable to application in the sphere of structured light [207], leading, for example, to the discovery that it is possible to deliver vortex photons by direct emission from suitably excited arrays [208][209][210] and so paving the way for a range of technical developments and implementations [211][212][213][214][215][216]. Whether the optical orbital angular momentum (OAM) of structured light could be transferred to the internal electronic degrees of freedom of an atom or molecule has been a well-debated topic, with highly significant implications in spectroscopy [217].…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%
“…In eliciting the physics for the majority of applications discussed above, it has generally proved sufficient to use plane-wave representations of the quantum radiation modes, together with their polarization properties. Nonetheless, the same QED methods are highly amenable to application in the sphere of structured light [207], leading, for example, to the discovery that it is possible to deliver vortex photons by direct emission from suitably excited arrays [208][209][210] and so paving the way for a range of technical developments and implementations [211][212][213][214][215][216]. Whether the optical orbital angular momentum (OAM) of structured light could be transferred to the internal electronic degrees of freedom of an atom or molecule has been a well-debated topic, with highly significant implications in spectroscopy [217].…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%
“…In addition, quantum entanglement of states with AM > 10000 has been observed in Ref. 34. Only recently there are attempts to manipulate the AM of twisted light by excitons 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…This technical progress makes it possible to employ excitons to efficiently process and manipulate information encoded in light by bridging the gap between photonics and electronics 56 . An exciton that is generated by illuminating a molecule with C N (N ≥ 3) symmetry by twisted light, for example, obtains the AM of the absorbed photon, and it turns out that a chain of such molecules can be used to create excitonic wave packets with well defined linear and angular momenta 35,36,57 . A succession of absorption events generates excitonic wave packets carrying a range of AM.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst beams of light with this vortex structure can routinely be produced by passing conventional Gaussian light through a variety of optical elements-notably spatial light modulators [76], it has been shown that rotationally symmetric chiral arrays can deliver vortex photons by direct emission [5,[77][78][79], as illustrated in figure 8. There is in fact a wide variety of other beams conveying orbital angular momentum, some including several kinds of modified-Gaussian vortex [80] described as having a perfect optical vortex structure [81], and others with the propagation-invariant character of Bessel beams [82].…”
mentioning
confidence: 99%